Enhancing Wound Healing Through Secretome-Loaded 3D-Printed Biomaterials - Tithteeya Rattanachot; Yogeswaran Lokanathan; Mh Busra Fauzi; Manira Maarof (Gels)
Wound healing remains a significant hurdle within the field of medical practice, especially concerning chronic and non-healing injuries. Conventional interventions, such as skin grafts, wound dressings, and biomaterials, offer structural support for the regenerated tissues but often lack the biological signaling cues essential for tissue regeneration. However, these approaches often lack the biological signals necessary to promote effective tissue repair. An emerging strategy involves incorporating cell-secreted proteins, known as the secretome, into biomaterials. The secretome contains bioactive elements such as cytokines, growth factors, and extracellular vesicles (EVs), which enhance the wound healing process. This review explores the potential of secretome-loaded biomaterials in modulating inflammation, promoting angiogenesis, and assisting in the remodeling of the extracellular matrix (ECM). Recent advancements in biomaterial engineering technology, such as 3-dimensional (3D) bioprinting, have improved the controlled delivery and bioactivity of secretome at the wound site. These gel-based biomaterials enhance wound healing by providing sustained bioactive molecule release, improving cell growth, and tissue repair. Despite these promising outcomes, limitations including variations in secretome composition and difficulties in large-scale production. Hence, secretome-loaded biomaterials offer a promising solution for wound healing, but further research is needed to optimize formulations, ensure stability, and validate clinical applications.